Pemanfaatan Limbah Plastik Dari Casing Printer Bekas Dengan Pra-Treatment 5% Naocl Dan 4% Naoh Sebagai Filler Dalam Pembuatan Batako Pejal - Bhaskoro A. Muthohar; Yusnimar Yusnimar; M. Iwan Fermi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Research on the use of plastic waste has been carried out in recent years, but the weak adhesivity between the surface of the plastic and cement make a drastic reduction in compressive strength in the cement-plastic mixture. To overcome this problem, treatment iscarried out on the plastic that has been chopped using 4% NaOCl and 5% NaOH to convert the polymeric hydrocarbon groups in the plastic into R-COOH which is more reactive to thecement material. In this research nine solid bricks are evaluated to study four ABS material composition using pra-treatment 4% NaOH and 5%NaOCl, and four without pra-treatment.Those four ABS material compositions total are 0; 0,2; 0,4; kg. The results showed substitution of 0.4 kg ABS with treatment succeeded in reducing the dry weight of the block by 21% and increasing the compressive strength of the block by 30%. This shows theresulting brick has better quality than the brick without substitution.Keywords : ABS substitution, acrylonitrile butadiene styrene, solid brick, recycled plastic